How Criminalization of Blasphemy on Social Media Intensifies Social Division: A Critical Criminology Perspective - Fany Nur Rahmadiana Hakim; Untung Sumarwan (Jurnal Kawistara, 2025)
Existing studies on Indonesia’s blasphemy law have primarily focused on its constitutional foundations and judicial interpretation, particularly through analyses of decisions by the Constitutional Court. This tudy examines the intricate dynamics of blasphemy laws in Indonesia, with a particular focus on their implications in the digital era. Building on this body of work, including Melisa Crouch’s influential study on law and religion in Indonesia, this article shifts attention to the practical criminalization of blasphemy in the context of social media. While these laws aim to protect religion and religious values, they often result in the criminalization of certain expressions, particularly in virtual spaces. This research scrutinizes the intersection between blasphemy laws and the Electronic Information and Transactions Law, highlighting the tensions between freedom of expression, the right to practice religion and belief, and the role of technology in modern legal frameworks. The primary analysis adopts a critical criminological perspective, suggesting that those in power can legislate and criminalize anyone. This study examines the impact of public perceptions on legal processes in blasphemy cases. Data collection techniques include searching and sorting related news articles and legal text documents. Thematic analysis is employed to uncover patterns and dynamics of power embedded in the narratives. The findings indicate how these legal tools exacerbate societal divisions and contribute to the escalation of inter-religious tensions, especially in the context of online content, reflecting broader sociopolitical dynamics and moral judgments. The research results underscore the need for a more nuanced  understanding of blasphemy law and a critical re-evaluation of its application, taking into account both legal and philosophical perspectives. The media plays an important role in shaping narratives and influencing judicial outcomes, emphasizing the intersection of law, media, and society in the context of blasphemy allegations.